2020
DOI: 10.3389/fmicb.2020.01352
|View full text |Cite
|
Sign up to set email alerts
|

Galactooligosaccharides and Resistant Starch Altered Microbiota and Short-Chain Fatty Acids in an in vitro Fermentation Study Using Gut Contents of Mud Crab (Scylla paramamosain)

Abstract: Dietary carbohydrates are anaerobically fermented by gut microbiota to shortchain fatty acids (SCFAs), conferring gut health benefits. Of all tested prebiotics, galactooligosaccharides (GOS) and resistant starch (RS) stimulated the SCFA production in mud crab (Scylla paramamosain), a crustacean model, to a greater extent than the other carbohydrates tested. Using in vitro anaerobic fermentation cultures, this study further explored the prebiotic potential of GOS and RS in mud crab by assessing their impacts on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…Specifically, oligosaccharides may be utilized by rumen bacteria to produce SCFA ( Cotta, 1993 ). Consistent with the present findings, in vitro fermentation studies have shown that GOS stimulate SCFA production, including that of acetic acid and propionic acid ( Tran et al., 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Specifically, oligosaccharides may be utilized by rumen bacteria to produce SCFA ( Cotta, 1993 ). Consistent with the present findings, in vitro fermentation studies have shown that GOS stimulate SCFA production, including that of acetic acid and propionic acid ( Tran et al., 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…The rumen acetate and propionate concentrations were higher in calves in the GOSC and GOSS groups than in the CON group. Previous studies have also shown that prebiotics, such as oligosaccharides, are capable of increasing rumen short chain fatty acid (SCFA) concentrations by promoting microbial fermentation in the gastrointestinal tract ( Yu et al, 2019 ; Tran et al., 2020 ). Specifically, oligosaccharides may be utilized by rumen bacteria to produce SCFA ( Cotta, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GOS also decreased the inflammatory markers IL-6, TNF-α, and IL-1β. The anti-inflammatory effect may be related to butyrate production as an in vitro study showed GOS increased butyrate production [47]. In a rotavirus infection suckling rat model, FOS and GOS reduced infectivity of the virus and symptoms in rats [48].…”
Section: Inulin Fos (Fructo-oligosaccharides) and Gos (Galacto-oligos...mentioning
confidence: 99%
“…It was also concluded that 90% of GOS resist digestion in the upper GIT and then enter the colon, which then get intact to the tract and act as fermentation substrates for the resident microbiota [ 162 ] ( Table 3 ). An in-vitro study showed that the fermentation of GOS by GM generates SCFAs and organic acids that decrease luminal pH, thereby enhancing the bioavailability of nutritionally important minerals [ 163 ]. Interestingly, GOS administration showed anxiolytic effects in both animals [ 164 ] and humans [ 165 ] ( Table 3 ).…”
Section: Efficacy Of Prebiotics On Gut Microbiota Composition: In Viv...mentioning
confidence: 99%